Case report: Rapid development of acute symptomatic portal vein system thrombosis after endoscopic variceal therapy in a patient with liver cirrhosis - Ran Wang; Xiaozhong Guo; Fangbo Gao; Yongguo Zhang; Qianqian Li; Siqi Jia; Xiaodong Shao; Xingshun Qi (Frontiers in Medicine, 2024)
Acute portal vein thrombosis (PVST), a serious complication of liver cirrhosis, is characterized as abdominal pain secondary to intestinal ischemia, and even intestinal necrosis. Anticoagulation is recommended for the treatment of acute PVST, but is often postponed in cirrhotic patients with acute variceal bleeding or those at a high risk of variceal bleeding. Herein, we reported a 63-year-old male with a 14-year history of alcoholic liver cirrhosis who developed progressive abdominal pain related to acute portal vein and superior mesenteric vein thrombosis immediately after endoscopic variceal ligation combined with endoscopic cyanoacrylate glue injection for acute variceal bleeding. Fortunately, acute PVST was successfully recanalized by the use of low molecular weight heparin. Collectively, this case suggests that acute symptomatic PVST can be secondary to endoscopic variceal therapy in liver cirrhosis, and can be safely and successfully treated by anticoagulation.